The Relationship of Nurses' Knowledge in the Use of Personal Protective Equipment (PPE) with the Incidence of Nasocomial Infections at the Dr. Rom. Djoelham Binjai 2020 - Aisyah (Science Midwifery, 2020)
Knowledge is the result of "knowing" that occurs after people sense a certain object, especially through the eyes and ears. Personal protective equipment is a tool used to protect oneself or the body against the dangers of work accidents. Infection is the entry and multiplication of microorganisms in the host's body that can cause illness. This type of research is a descriptive study using a cross sectional study design. The purpose of this research is to determine the relationship between knowledge of nurses in the use of personal protective equipment (PPE) with the incidence of Nasocomial Infections at the Dr. RM. Djoelham Binjai in 2020. In this study, the number of samples was 32 people. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000 < 0 0.05), it can be seen that there is a relationship between knowledge of nurses in the use of personal protective equipment (PPE) with the incidence of Nasocomial Infections at the Dr. RM. Djoelham Binjai in 2020. This research is expected to provide input to the hospital management, which is expected to provide information on how important it is to use personal protective equipment to prevent infection. 05) it can be seen that there is a relationship between the knowledge of nurses in the use of personal protective equipment (PPE) with the incidence of Nasocomial Infections at the Dr. RM. Djoelham Binjai in 2020. This research is expected to provide input to the hospital management, which is expected to provide information on how important it is to use personal protective equipment to prevent infection. 05) it can be seen that there is a relationship between the knowledge of nurses in the use of personal protective equipment (PPE) with the incidence of Nasocomial Infections at the Dr. RM. Djoelham Binjai in 2020. This research is expected to provide input to the hospital management, which is expected to provide information on how important it is to use personal protective equipment to prevent infection.